(untitled) (Heteroglossia – studia kulturoznawczo-filologiczne, 2019)
The article characterizes the main features Bocheński’s conception of Analytic Philosophy. In the first part, we present the difference between Analytic Philosophy and different world-views. Then we discuss the forth rules of analysis, and finally we refer to the practical and social role of Analytic Philosophy pointed out by Bocheński.